SOCIAL WORK PERCEPTIONS OF PEDOPHILES: OPENING THE DIALOGUE - Montes, Dana Rose (2018)
Pedophiles are the most stigmatized population in society (Jahnke, Imhoff, & Hoyer, 2015; Sanghara & Wilson, 2006). Social worker’s responsibility is to maintain standards and treat individuals with dignity and respect (NASW, 2017). It is important to explore bias against pedophiles because studies have shown bias is linked to offender recidivism rates (Jahnke, Schmidt, Geradt, & Hoyer, 2015). Social workers may unintentionally inhibit pedophiles from seeking treatment if they hold strong biases against them which could potentially negatively impact child abuse rates. The purpose of this study was to identify bias reduction techniques so that they could possibly be implemented in the social work field. Experienced social workers and social work students were interviewed so that the origins of and methods to combat bias could be explored. Themes among interviewee responses were identified and the importance of Opening a Dialogue eclipsed the need to utilize bias reduction techniques